2016
DOI: 10.1590/0001-3765201620140490
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of simvastatin throught oxidative imbalance caused by lisdexamfetamine dimesylate

Abstract: The present study aims to directly investigate the behavioral and antioxidant effects of simvastatin in a model of bipolar mania induced by lisdexamfetamine dimesylate. Wistar rats were treated for 30 days with simvastatin. On the 24th day after the start of treatment, each rat was administered lisdexamfetamine dimesylate for 7 days. The results suggest that simvastatin combined with lisdexamfetamine dimesylate induced a signifi cant increased locomotion and lisdexamfetamine dimesylate administration causes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…2). The lipid lowering (Garcia et al, 2016), antioxidant (Eger et al, 2016) and antiinflammatory (Al-Ani, 2013) effects of simvastatin and the presence of polyphenolic antioxidants, flavonoids, oligomeric flavonoids (proanthocyanidins), and catechins (Kim et al, 2000) in the hawthorn plant could be the reason for the observed substantial treating effects of Crataegus aronia and simvastatin and a better architecture of liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…2). The lipid lowering (Garcia et al, 2016), antioxidant (Eger et al, 2016) and antiinflammatory (Al-Ani, 2013) effects of simvastatin and the presence of polyphenolic antioxidants, flavonoids, oligomeric flavonoids (proanthocyanidins), and catechins (Kim et al, 2000) in the hawthorn plant could be the reason for the observed substantial treating effects of Crataegus aronia and simvastatin and a better architecture of liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin, vitamin C, and BCSO can serve as antioxidants and immunomodulators [23,26,27]. BCSO administration with equivalent dose of thymoquinone 68 mg/kgBW shows lower levels of MDA.…”
Section: Blood Malondialdehyde Levelmentioning
confidence: 99%
“…a p < 0.05 compared to all other groups. 2015; Eger et al, 2016), as observed in plasma as well as serum of bipolar patients in manic state (Machado-Vieira et al, 2007;Caldiroli et al, 2020). Thus, the LDX model is a valid procedure for the study of mania and antimanic-like drugs.…”
Section: Discussionmentioning
confidence: 90%
“…LDX is a long-acting pro-drug of d-amphetamine employed in the therapeutic management of attention deficit/hyperactivity disorder (Ermer et al, 2016). LDX administration has also been used to mimic manic-like behavior in animals (Macêdo et al, 2013;de Souza et al, 2015;Eger et al, 2016;Wendler et al, 2016;Ascoli et al, 2017;Bristot et al, 2019). These manic-like behaviors were reversed or prevented by treatment with lithium or valproate (Macêdo et al, 2013;de Souza et al, 2015;Wendler et al, 2016;Ascoli et al, 2017;Bristot et al, 2019).…”
Section: Discussionmentioning
confidence: 99%